Towards Enterprise Sustainable Innovation Process: Through Boundary-Spanning Search and Capability Reconfiguration - Ning Cao (MDPI AG, 2021)
In the open innovation environment, enterprise sustainable innovation is no longer the result of individual decision-making. Extensive contact with suppliers, customers, scientific research institutions, and other subjects for boundary-spanning knowledge search, absorption, and reconfiguration is considered a critical path to enterprise sustainable innovation. Studying the process of “how boundary-spanning search affects enterprise sustainable innovation” has become an urgent and valuable task. Therefore, based on an innovation search perspective, this study explored the path and mechanism of boundary-spanning search affecting enterprise sustainable innovation, revealed the intermediary effect of capability reconfiguration, and clarified the regulatory role of information technology (IT) governance. We also proposed an integrated model promoting enterprise sustainable innovation process. Using questionnaire data from manufacturing companies in China, this study empirically tested the proposed model hypothesis. The results demonstrated that all boundary-spanning searches (supply-side, demand-side, and cross-regional searches) positively and significantly impacted enterprise sustainable innovation. However, the effects of the search types varied. Capability reconfiguration played a partial intermediary role between boundary-spanning search and enterprise sustainable innovation. IT governance positively moderated the relationship between boundary-spanning search and enterprise capability reconfiguration, particularly between cross-regional search and enterprise capability reconfiguration. This study enriches our understanding of the sustainable innovation process and provides theoretical guidance for enterprises to improve their sustainable innovation performance by effectively using boundary-spanning search strategies.